Distribution, size and density of Corbicula ﬂuminea at Pattani and Saiburi rivers in Southern Thailand - Mohamad Shamsul, Zaween Najjah; Eh Rak, Aweng; Hajisamae, Sukree (2017)
Abstract: Corbicula fluminea has been a traditional food for the locals from both Kelantan and Southern Thailand. However, the ecology of C. fluminea has not been fully explored in Malaysia and also in Southern Thailand. The objective of this study is to compare the size and density of C. p ﬂuminea in Pattani and Saiburi rivers. C. ﬂuminea were sampled in two different rivers at Southern Thailand; Pattani River and Saiburi River. The water quality parameters measured are dissolved oxygen, pH, temperature and the nutrient analysis of phosphate and nitrate. Both rivers have a suitable pH levels range (6.53-6.7), temperature range (31-34°C) and dissolved oxygen (3.3-8.1 mg/L) that ensure the survival of C. ﬂuminea. C. ﬂuminea were collected and measured its shell length which is most abundant in length size ll-20 mm. The highest density of C. ﬂuminea recorded at Pattani River was 369 clams per, m2 while only 196 per m2 at Saiburi River. The over-exploitation by the villagers at Saiburi River has caused the density of C. fluminea to differ signiﬁcantly. The substrate type of these rivers were also anal- ysed; Pattani River has sandy loam substrate while the substrate in Saiburi River is loamy sand. The availability of the phytoplankton was also identiﬁed in both rivers and overall there were 29 species from 22 different families in both rivers. This study shows that the density of C. ﬂuminea is likely to be inﬂuenced by the water quality rather than substrate types and also the phytoplankton availability. Findings of this research are able to add to the existing database of C. ﬂuminea nationally and internationally. Key words: Corbicula ﬂuminea, habitat, water quality, sediment, phytoplankton, Pattani River, Saiburi River